DIETARY EFFECT OF SUGARCANE PRESS MUD ON GROWTH PERFORMANCE, NUTRIENT UTILIZATION, RUMEN FERMENTATION AND BLOOD PROFILE STATUS OF GROWING CROSSBRED CALVES - M. Palanivel (Indian Journal of Veterinary and Animal Sciences Research, 2025)
Sugarcane press mud (SPM) is one of the potential agro-industrial by-products available in India and research exploring its utilisation in ruminant nutrition is scanty. In this direction, the present study evaluated the feasibility of dietary incorporation of SPM at graded levels in a feeding trial lasting 180 days to crossbred growing calves. A total of 18 numbers ofJersey crossbred growing calves were randomly distributed into three groups of six each based on comparable body weight (90.70±3.43Kg) and age (~5 Months) following a completely randomised design. The three dietary treatments were SP0, concentrate mixture without SPM; SP10, concentrate mixture comprising 10% SPM and SP20, concentrate mixture comprising 20% SPM on air-dry basis.The experimental calves were offered weighed quantity of designated isonitrogenous and isoenergetic concentrate mixture (coarse mash) along with ad libitum Co-FS 29 (chopped to 1-2 cm length) to fulfil nutrient requirements prescribed by Indian Council of Agriculture and a 6 days digestion trial was conducted towards end of the feeding trial. Representative pooled sub-sample of daily collected and acid preserved urine samples were analysed for purine derivatives to assess the microbial N supply to host animals. Blood samples were collected on 0, 60, 120,and 180 day of experiment to assess the metabolic status of growing calves. Results revealed no significant (P>0.05) differences in the intake and digestibility of basal nutrients, nitrogen balance, nutritive value of diets, average daily gain as well as feed conversion ratio among the treatment groups. Dietary Caretained by growing calves was significantly (P0.05) among the treatments. The cost of formulated concentrate mixture (Rs/day) was reduced (P